BS EN 17038-4. Pumps. Methods of qualification of the Energy Efficiency Index for rotodynamic pump units. Part 4. Testing and calculation of energy efficiency index (EEI) of submersible multistage pump units (12th August 2021) - British Standards Institution,
No abstract available